Educação para a virtualidade - Costa, André Pereira da (Boletim Técnico do Senac, 2003)
Education, as considered and most of all applied in school contexts, and regarding this ‘foolish world’ in which we all live, requires radical transformations. The article presents some challenges that must be urgently faced, from the search for qualitatively different ways to react to the problems that reality poses nowadays to the rejection of the traditional "four walls pedagogy"; from the teacher’s qualification to deal with new educational processes to the conception and development of educational communications capable of incorporating simultaneity and interactivity -both central to multimedia technology production.